2017
DOI: 10.1038/s41598-017-17425-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Yagi-Uda antenna based on a silicon reflector with a solid-state plasma

Abstract: This paper describes the fabrication and characterization of a reconfigurable Yagi-Uda antenna based on a silicon reflector with a solid-state plasma. The silicon reflector, composed of serially connected p-i-n diodes, forms a highly dense solid-state plasma by injecting electrons and holes into the intrinsic region. When this plasma silicon reflector is turned on, the front-realized gain of the antenna increases by more than 2 dBi beyond 5.3 GHz. To achieve the large gain increment, the structure of the anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Moreover, it is difficult to design an antenna due to embedded metallic elements, such as bias lines and gold wires, for applying DC bias. We overcame these problems in previous studies and showed that silicon material can be used as a reflector for a Yagi–Uda antenna 20 . However, the success of the silicon reflector only implies that the silicon has enough conductivity to simply reflect an incoming wave.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is difficult to design an antenna due to embedded metallic elements, such as bias lines and gold wires, for applying DC bias. We overcame these problems in previous studies and showed that silicon material can be used as a reflector for a Yagi–Uda antenna 20 . However, the success of the silicon reflector only implies that the silicon has enough conductivity to simply reflect an incoming wave.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the low carrier concentration caused by low voltage will lead the SSP to an unexcited eigenstate with little ability to carry the EMW (equivalent to dielectric). Therefore, the exceptional reconfigurability can be obtained by artificially inspiring SSP with various structures and positions [20]- [22].…”
Section: And Advancedmentioning
confidence: 99%
“…Further, based on State II, when two L-shaped SSP resonators on the second layer are also motivated (we call this case State III), the corresponding operating band will be shifted to the low-frequency region while holding on the function of State II. + jωω c ) [20]- [22]. The plasma frequency of two helical and four L-shaped SSP patches are ω p1 = 2.9 × 10 14 rad/s and ω p2 = 1.2 × 10 15 rad/s, respectively.…”
Section: Structure Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid state plasma (SSP) [26][27][28] has excellent reconfigurable characteristics and can be integrated with an RF front-end system. Its structure dimension has greater freedom for realizing the multi-function, miniaturization, and integration of the whole system, which is quite suitable for microwave devices.…”
Section: Introductionmentioning
confidence: 99%